STUDI HARI PERDAGANGAN SAHAM-SAHAM KELOMPOK SEKTOR PERTANIAN YANG LISTING DI BURSA EFEK INDONESIA - Widodo, Purwanto (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
This research intent to test Efficient Market Hypothesis (EMH) that interposed by Fama (1970) notably tests to hit phenomenon trade day. The data that is used is emiten that listing at Indonesian Stock Exchange (BEI) period January – December 2009. Examination is The Day Of The Week Effect's effect and week four effect. Meanwhile analisis which is used is Multivariate Multivariate Analysis of Variance (MANOVA) and one sample is test . Result observationaling to point out that not return AALI'S stock, IIKP, UNSP and LSIP doesn't point out to pattern particular, and examination result with MANOVA and also one sample is test not also seeming marks sense The Day Of The Week Effect and week four effect.